1997
DOI: 10.1021/jm970397q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Series of Potent and Orally Bioavailable Thrombin Inhibitors That Utilize 3,3-Disubstituted Propionic Acid Derivatives in the P3 Position

Abstract: As part of an effort to prepare efficacious and orally bioavailable analogs of the previously reported thrombin inhibitors 1a, b, we have synthesized a series of compounds that utilize 3,3-disubstituted propionic acid derivatives as P3 ligands. By removing the N-terminal amino group, the general oral bioavailability of this class of compounds was enhanced without excessively increasing the lipophilicity of the compounds. The overall properties of the molecules could be drastically altered depending on the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…[5][6][7] This pronounced effect was also observed for other sterically demanding substituents such as pyridine 7 and cyclohexane. 8 Bis(phenyl)methane inhibitors that do not interact with residues in the S1 pocket of thrombin have been described.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…[5][6][7] This pronounced effect was also observed for other sterically demanding substituents such as pyridine 7 and cyclohexane. 8 Bis(phenyl)methane inhibitors that do not interact with residues in the S1 pocket of thrombin have been described.…”
Section: Introductionmentioning
confidence: 61%
“…Consequently, the current systematic experimental study has been carried out in order to find a rationale for the previously reported boost in inhibitory potency in the case of bis(phenyl)methane ligands. [5][6][7] This study covers a series of six related inhibitors ( Fig. 1) for which the hydrophobic substituent that binds into the thrombin S3 pocket is increased in a stepwise fashion by the addition of phenyl rings to the central core structure.…”
Section: Introductionmentioning
confidence: 99%
“…Negligible activity was determined for inhibitor 16 containing trans-4amidomethylcyclohexylamine, although this P1 group is well suited for the design of thrombin inhibitors. [30,32] However, its conversion into a guanidine residue in analogue 17 provided the most potent inhibitor of this first series, possessing a K i value of 1.2 mm.…”
Section: Enzyme Kineticsmentioning
confidence: 96%
“…82 Removal of the N-terminus amino group led to 44 (Ki ¼ 2 nM) which not only enhanced the oral bioavailability of this class in rats and dogs but also has excellent pharmacokinetics (t 1/2 ¼ 2.5 hr). 83 The group at Merck have mad use of combinatorial chemistry to synthesize more than 200 varients of 44 to obtain compound 45 (L-372,460, Ki ¼ 1.5 nM) 84 which showed good efficacy and significant oral bioavailability in dogs and monkeys.…”
Section: B Reversible Covalent Thrombin Inhibitorsmentioning
confidence: 99%